To a common missionary testimony: possibilities and limits. A holy and great council of the orthodox Church, point of view (Religious dialogue and cooperation, 2020)
In the framework of the World Council of Churches and inthe bilateral theological dialogues between diverse Churches anddenominations, the question of a common missionary testimony is aquite often topic. Since 2016, when the Holy and Great Council of theOrthodox Church was held, a new perspective showed up regardingthe Orthodox point of view. The following study tries to underlinethe ecumenical perspective of how Churches and denominationsmay or may not work together in the spirit of missionary testimonyinto the world. The newest documents provided by the OrthodoxChurch may give some new hopes in this respect.
Keywords: mission; confessional; Orthodoxy; Church; testimony mission